Towards development of treat to target (T2T) in childhood-onset systemic lupus erythematosus: PReS-endorsed overarching principles and points-to-consider from an international task force - Smith, Eve Mary Dorothy; Aggarwal, Amita; Ainsworth, Jenny; Al-Abadi, Eslam; Avcin, Tadej; Bortey, Lynette; Burnham, Jon; Ciurtin, Coziana; Hedrich, Christian M; Kamphuis, Sylvia; Levy, Deborah M; Lewandowski, Laura B; et al. (Elsevier, 2023)
Objectives Application of 'treat-to-target' (T2T) in childhood-onset systemic lupus erythematosus (cSLE) may improve care and health outcomes. This initiative aimed to harmonise existing evidence and expert opinion regarding T2T for cSLE. Methods An international T2T Task Force was formed of specialists in paediatric rheumatology, paediatric nephrology, adult rheumatology, patient and parent representatives. A steering committee formulated a set of draft overarching principles and points-to-consider, based on evidence from systematic literature review. Two on-line preconsensus meeting Delphi surveys explored healthcare professionals' views on these provisional overarching principles and points-to-consider. A virtual consensus meeting employed a modified nominal group technique to discuss, modify and vote on each overarching principle/point-to-consider. Agreement of >80% of Task Force members was considered consensus. Results The Task Force agreed on four overarching principles and fourteen points-to-consider. It was agreed that both treatment targets and therapeutic strategies should be subject to shared decision making with the patient/caregivers, with full remission the preferred target, and low disease activity acceptable where remission cannot be achieved. Important elements of the points-to-consider included: aiming for prevention of flare and organ damage; glucocorticoid sparing; proactively addressing factors that impact health-related quality of life (fatigue, pain, mental health, educational challenges, medication side effects); and aiming for maintenance of the target over the long-term. An extensive research agenda was also formulated. Conclusions These international, consensus agreed overarching principles and points-to-consider for T2T in cSLE lay the foundation for future T2T approaches in cSLE, endorsed by the Paediatric Rheumatology European Society.
Keywords: Autoimmune Diseases; Glucocorticoids; Health services research; Lupus Erythematosus, Systemic; Outcome and Process Assessment, Health Care